'Game changer or another dummy': Media appraisals of government policies. Issue 2 (6th September 2019) - Jakaza, Ernest
Abstract: Policies and/or constitutional provisions are a cornerstone for the development of a country. Varied language-related policies and constitutional acts have been crafted and/or amended in an effort to redress the language inequalities in Zimbabwe. The enactment of the new constitution in 2013 saw 16 languages accorded the status of officially recognised language. The media's role in publicising these constitutional provisions, and 'digesting' them for the heterogeneous audience, is vital for the development of the country. The article argues that subjectivities in the news reporting of a country's enactment of a new language policy are detrimental to the implementation, realisation and overall acceptance of the policy. The article employs the appraisal theoretical framework to examine the print media's evaluations of the Zimbabwean government's constitution. Major focus is on the print media appraisals of the Zimbabwean constitutional provisions and their implementation. Utilising the qualitative research paradigm, news reports from Zimbabwe's print media are purposively sampled. A discourse-analytic design is employed. The research concludes that even though they are other factors, the Zimbabwean print media, both independent and government, positively appreciated [+ve appreciation] the country's constitutional language provisions for the development of previously marginalised languages.